Dysregulation of ubiquitin ligases in cancer - Qi, Jianfei; Ronai, Ze’ev A. (Drug resistance updates, 2015)
Ubiquitin ligases (UBLs) are critical components of the ubiquitin proteasome system (UPS), which governs fundamental processes regulating normal cellular homeostasis, metabolism, and cell cycle in response to external stress signals and DNA damage. Among multiple steps of the UPS system required to regulate protein ubiquitination and stability, UBLs define specificity, as they recognize and interact with substrates in a temporally- and spatially-regulated manner. Such interactions are required for substrate modification by ubiquitin chains, which marks proteins for recognition and degradation by the proteasome or alters their subcellular localization or assembly into functional complexes. UBLs are often deregulated in cancer, altering substrate availability or activity in a manner that can promote cellular transformation. Such deregulation can occur at the epigenetic, genomic, or post-translational levels. Alterations in UBL can be used to predict their contributions, affecting tumor suppressors or oncogenes in select tumors. Better understanding of mechanisms underlying UBL expression and activities is expected to drive the development of next generation modulators that can serve as novel therapeutic modalities. This review summarizes our current understanding of UBL deregulation in cancer and highlights novel opportunities for therapeutic interventions.